The Impact of the FLPP Program on Improving Community Welfare through Subsidized Home Ownership - Faisal Akbar (Journal of Economics, Management, Development, and Education, 2026)
This study aims to analyze the impact of the Housing Financing Liquidity Facility Program (FLPP) onimproving community welfare through subsidized home ownership. The FLPP program is a government policy aimedat providing access to affordable housing financing for low-income communities (MBR). This study uses a descriptivequalitative approach, with data collection techniques including interviews, observation, and documentation. Theresearch informants consisted of community recipients of subsidized housing, housing developers, and banksdistributing the FLPP program. The research results show that the FLPP Program has a positive impact on improvingcommunity welfare, particularly in economic, social, and psychological aspects. From an economic perspective,people experience a reduction in expenses because they no longer have to pay rent. From a social perspective, homeownership improves family stability and social participation in the community. Meanwhile, from a psychologicalperspective, people feel an increased sense of security and life satisfaction after owning their own home. However,this study also found several obstacles in the implementation of the FLPP program, such as limited subsidizedhousing quotas, less strategic housing locations, and an administrative process that some people still find quitecomplex. Overall, the FLPP program is considered to have made a positive contribution to improving communitywelfare, although improvements in implementation are still needed to optimize and distribute its benefits more evenly.